2015
DOI: 10.1080/02699931.2015.1034091
|View full text |Cite
|
Sign up to set email alerts
|

Happiness increases verbal and spatial working memory capacity where sadness does not: Emotion, working memory and executive control

Abstract: The effects of emotion on working memory and executive control are often studied in isolation. Positive mood enhances verbal and impairs spatial working memory, whereas negative mood enhances spatial and impairs verbal working memory. Moreover, positive mood enhances executive control, whereas negative mood has little influence. We examined how emotion influences verbal and spatial working memory capacity, which requires executive control to coordinate between holding information in working memory and completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 56 publications
7
44
0
2
Order By: Relevance
“…Additional assessments were completed (at the beginning of the visit) to ensure that conditions were similar on these parameters. To assess mood status, which may influence memory capacity [46], participants completed the Positive and Negative Affect Schedule (PANAS) [47]. For this mood survey, participants rated 20 items (e.g., excited, upset, irritable, attentive) on a Likert scale (1, very slightly or not at all; to 5, extremely), with half of the items constituting a "positive" mood state, with the other half being a "negative" mood state.…”
Section: Additional Assessmentsmentioning
confidence: 99%
“…Additional assessments were completed (at the beginning of the visit) to ensure that conditions were similar on these parameters. To assess mood status, which may influence memory capacity [46], participants completed the Positive and Negative Affect Schedule (PANAS) [47]. For this mood survey, participants rated 20 items (e.g., excited, upset, irritable, attentive) on a Likert scale (1, very slightly or not at all; to 5, extremely), with half of the items constituting a "positive" mood state, with the other half being a "negative" mood state.…”
Section: Additional Assessmentsmentioning
confidence: 99%
“…A tarefa de n-back foi incluída em dois artigos (Lindström & Bohlin, 2011;Hur, Iordan, Dolcos, & Berenbaum, 2016). Outros artigos contemplaram tarefas de span simples que mediam a memória de curto prazo (Bergmann, Rijpkema, Fernandez, & Kessels, 2012;Fairfield, Mammarella, Domenico, & Palumbo, 2014;Esmaeili, Karimi, Tabatabaie, Moradi, & Farahini, 2011;Gotoh, 2012;Gotoh, Kikuchi & Olofsson, 2010;Xie & Zhang, 2016), Operation Span Task -OSPAN (Storbeck & Maswood, 2015), e o método de interferência seletiva (Levens & Phelps, 2008) vinculados ao modelo de Baddeley.…”
Section: Artigos Com Delineamento Estritamente Comportamentaisunclassified
“…Usando uma tarefa de discriminação de cores e de detecção de alvo com palavras afetivas com retro-pistas espaciais, Gotoh et al (2010) descobriram que estímulos negativos geraram tempos de resposta mais curtos em comparação com os estímulos verbais neutros e positivos. Em outro artigo, Gotoh (2012) Considerando a linha conceitual que suporta os resultados dos trabalhos apresentados, dois dos dez artigos (Fairfield et al, 2014;Xie & Zhang, 2016) (Hur et al, 2016;Levens & Phelps, 2008;Lindström & Bohlin, 2011;Storbeck & Maswood, 2015;Gotoh, 2012;Gotoh et al, 2010)…”
Section: Artigos Com Delineamento Estritamente Comportamentaisunclassified
“…Emotions are related to motivational processes, self-efficacy, and active engagement, each of which has a salient role in productive learning in schooling contexts (Pekrun, Elliot & Maier, 2006). In research on adult learning, positive emotions have been found to broaden the scope of perception, whereas anxiety and fear have been connected to a narrowing of the perception and curiosity necessary for active and agentic learning (Fredrickson & Branigan, 2002;Perry, 2006;Storbeck & Maswood, 2015;Sung & Yih, 2015). In team-based learning, social and self-conscious emotions such as compassion, love, shame, anxiety, and anger have been found to influence how team members see each other, and how they perceive the future of the team (Homan, Van Kleef & Sanchez-Burks, 2015).…”
Section: Introductionmentioning
confidence: 99%